DIDACTIC INNOVATION IN THE COMPREHENSION OF TEXTS IN SECONDARY EDUCATION: PERCEPTIONS OF PERUVIAN TEACHERS - Delgado Davila, Heiser Joel (2024)
The purpose of the study was to analyze the perceptions of teachers from an educational institution regarding text comprehension and didactic innovation. Using a qualitative method, the interview technique mediated by a semi-structured question guide was used to collect information. Said instrument was oriented to consult concepts, group experience, organization and planning of teachers in the area of ​​communication. The findings show that the causes of a deficient management of reading competence are the low mastery of reading strategies and the role played by innovation in the educational field. Likewise, it was possible to conclude on the important performance of the teacher as a spokesperson for techno-didactic issues, facing the advances of the technique that bring with them some advantages and disadvantages due to the presence of artificial intelligence and excessive use tempting the new generations.